The Bear Grylls Adventure. Book 1, The Blizzard Challenge [anglicky] - Grylls, Bear (Bear Grylls Ventures, 2019)
New from the hugely popular survival expert and chief scout, Bear Grylls, comes a collectible series for young readers, that follows a different child on an outdoor activity camp. The first adventure, "Blizzard Challenge" includes adventure, survival skills, snowstorms and a magic compass.